John James Meikle and the Problem of the Wrongly Convicted: An Enquiry into the History of Criminal Appeals in New Zealand - Finn, Jeremy (Victoria University of Wellington Law Review, 2010)
This article investigates the development of the law governing of appeals in criminal cases in New Zealand, and the substantial though neglected history of agitation for recourse for the wrongly convicted. It uses as a lens the story of John James Meikle, a farmer convicted of sheep stealing in 1887, who later successfully prosecuted the principal prosecution witness for perjury, successfully petitioned Parliament for compensation, was the subject of a Royal Commission into his conviction and, uniquely, was declared innocent by an Act of Parliament in 1908. Meikle’s case was one of several highly publicised cases in the period 1880-1910 which demonstrated serious shortcomings in the law and led to parliamentary and public calls for reform. By 1910, calls for enactment of legislation on the lines of the Court of Criminal Appeal (established 1907) received wide supporting in parliament and from the judiciary. The article concludes by looking at the reasons why, despite this level of consensus, reform legislation was delayed until 1945.